A Framework for Construction-related Risks by integrating the Fuzzy Grey Comprehensive Evaluation Method (FGCE) - Jalhoom, Rana Jabbar Kasid; Mahjoob, Ahmed Mohammed Raoof (Engineering, Technology & Applied Science Research, 2024)
There are five basic phases for construction projects: planning, design, tendering, construction and maintenance. The risks of each phase have an impact on time, cost, and quality. In this paper, the tendering phase of the residential complex project was investigated as a case study, and the creation of a fuzzy and grey correlation analysis model was examined using a fuzzy theory and a grey correlation theory to dispel the professional judgment around the project phase. Creating a comparison and a reference matrix based on grey theory and/by examining factors and their impact on duration, cost, and quality separately, gives the construction investors a scientific, direct, flexible, and adaptable technique to assess project risks. The described method categorized the tendering phase risk based on the three project determinants: duration, cost, and quality. The correlation degree is greater than 0.5, hence construction project duration risk is almost nonexistent. The project investor must also investigate risk assumption, reduction, diversion, and evasion tactics to handle cost and quality risks, which are between 0.2 and 0.5. This suggests that tender phase issues do not affect project length but do affect cost and quality, requiring attention and action.